Making Cervical Screening More Accessible: A Compassion-Focused Self-Help Intervention for Survivors of Sexual Assault - Jane Smallwood BSc, MSc, PGCert, DClinPsy; Stuart Gibson PhD; Jill Zelin MBBCH, FRCOG, FSRH; Dawn Langdon MA, MPhil, PhD, CPsychol, FBPS; Jane Vosper BSc, MSc, PhD, DClinPsy (Journal of Patient Experience)
Female survivors of sexual assault may be at greater risk of cervical cancer than those with no such experience but are less likely to attend their cervical screening. This feasibility study evaluated a novel self-help intervention delivered via mobile app, designed to make cervical screening more accessible by addressing barriers commonly experienced by this group. Participants accessed the intervention immediately (n = 15) or were allocated to a control group (n = 15). Measures of shame, self-compassion, self-efficacy related to cervical screening, and progress toward attendance were completed at baseline and after 7 weeks. Significantly more participants in the intervention group booked and completed a cervical screening compared to controls. A significant group × time interaction was found for self-efficacy with a large effect size. No significant interactions were found for shame or self-compassion. Feedback was generally positive. The app appeared to be a feasible and acceptable way of providing self-help materials and was successful in increasing some participants’ confidence in their ability to attend a cervical screening, and in some cases led to attendance. Further evaluation is needed.